Motion Graphic Dalam Perancangan Media Promosi Produk Suplemen Di Starsfits - Agnes Christin Evyanti Simbolon; Fadli Suandi (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2022)
fitness supplements that require promotional media because many people do not know about Starsfits. So that motion graphics are made as promotional media which is one form of information media on technological developments. The design of this motion graphic video aims to introduce supplement products at Starsfits which are expected to be able to attract consumer interest as an effort to increase sales of supplement products at Starsfits. Motion graphics in promotional videos for supplement products at Starsfits were created using the Villamil-Molina version of the multimedia design method which consists of stages of development, preproduction, production, postproduction, and delivery. Based on the analysis of the motion graphic video, it has met the feasibility indicators for the application of motion graphic aspects, namely Spatial, Temporal, Live Action and Typography which got 4.36 results which are included in the very feasible (SL) category. Then an EPIC model analysis was conducted to determine the effect and effectiveness of the promotional video for supplement products at Starsfits. The conclusions from the analysis of the EPIC model are: (1) Empathy dimension 4.88, (2) Persuation 4.76, (3) Impact 4.85, (4) Communication 4.87, so that motion graphics in promotional videos for supplement products at Starsfits is stated to be very effective as a promotional medium.